Factors Related to Parent Attendance at a Follow-Up Meeting With an Intensivist After a Child's Death in the Pediatric Intensive Care Unit. (September 2019) - Suttle, Markita L.; Gerhardt, Cynthia A.; Fults, Marci Z.
Parents who experience the death of a child are at high risk for psychopathology. Because a large percentage of pediatric deaths occur in the pediatric intensive care unit each year, a follow-up meeting between bereaved parents and intensivists could provide essential emotional support, although some parents may not attend. The aim of this study was to explore demographic and medical factors that may distinguish between bereaved parents who attend a follow-up meeting with their child's pediatric intensivist and those who do not. Our analysis revealed that parents of children who died of trauma were less likely to attend a follow-up meeting with an intensivist. It is possible that symptoms of posttraumatic stress play a role in these findings. Enhanced efforts to identify other interventions for this specific subset of bereaved parents may be necessary.